ROADMAP PARA UMA ABORDAGEM ESTRATÉGICA PELA FUNÇÃO MANUTENÇÃO - Barros, Jorge Ferreira do Rego (2009)
Technological evolution and industrial growth followed by intensive self operating system and sophisticated equipment applications were responsible for maintenance function to develop models, management systems and engineering practice employment in order to be in attendance with open world competition demand. Regarding this environment, the general objective of this study is to introduce the leading position reached by maintenance in the enterprise strategic scenario to achieve its performance, profit and survival. In a bibliographic and explanatory approach, this research analyses patterns, ideas, techniques and facts through causal relationships among them in order to present maintenance as a business center, with relevant influence in all physical asset life cycle stages and proposes a roadmap for strategical maintenance function planning, which results will reflect on the strategical enterprise performance measured through a Balanced Scorecard system.